Sequence-Based Characterization of Tn5801-Like Genomic Islands in Tetracycline-Resistant Staphylococcus pseudintermedius and Other Gram-positive Bacteria from Humans and Animals - de Vries, Lisbeth E.; Hasman, Henrik; Jurado Rabadán, Sonia; Agersø, Yvonne (Frontiers in Microbiology, 2016)
Antibiotic resistance in pathogens is often associated with mobile genetic elements, such as genomic islands (GI) including integrative and conjugative elements (ICEs). These can transfer resistance genes within and between bacteria from humans and/or animals. The aim of this study was to investigate whether Tn5801-like GIs carrying the tetracycline resistance gene, tet(M), are common in Staphylococcus pseudintermedius from pets, and to do an overall sequences-based characterization of Tn5801-like GIs detected in Gram-positive bacteria from humans and animals. A total of 27 tetracycline-resistant S. pseudintermedius isolates from Danish pets (1998-2005) were screened for tet(M) by PCR. Selected isolates (13) were screened for GI- or ICE-specific genes (intTn5801 or xisTn916) and their tet(M) gene was sequenced (Sanger-method). Long-range PCR mappings and whole-genome-sequencing (Illumina) were performed for selected S. pseudintermedius-isolates (7 and 3 isolates, respectively) as well as for human Staphylococcus aureus isolates (7 and 1 isolates, respectively) and one porcine Enterococcus faecium isolate known to carry Tn5801-like GIs. All 27 S. pseudintermedius were positive for tet(M). Out of 13 selected isolates, 7 contained Tn5801-like GIs and 6 contained Tn916-like ICEs. Two different Tn5801-like GI types were detected among S. pseudintermedius (Tn5801 and GI6287) - both showed high similarity compared to GenBank sequences from human pathogens. Two distinct Tn5801-like GI types were detected among the porcine E. faecium and human S. aureus isolates (Tn6014 and GI6288). Tn5801-like GIs were detected in GenBank-sequences from Gram-positive bacteria of human, animal or food origin worldwide. Known Tn5801-like GIs were divided into 7 types. The results showed that Tn5801-like GIs appear to be relatively common in tetracycline-resistant S. pseudintermedius in Denmark. Almost identical Tn5801-like GIs were identified in different Gram-positive species of pet and human origin, suggesting that horizontal transfer of these elements has occurred between S. pseudintermedius from pets and human pathogens, including S. aureus.